1, 5‐Disubstituted 1, 2, 3‐Triazole‐Containing Peptidotriazolamers: Design Principles for a Class of Versatile Peptidomimetics. Issue 4 (13th December 2017) - Kracker, Oliver; Góra, Jerzy; Krzciuk‐Gula, Joanna; Marion, Antoine; Neumann, Beate; Stammler, Hans‐Georg; Nieß, Anke; Antes, Iris; Latajka, Rafał; Sewald, Norbert
Abstract: Peptidotriazolamers are hybrid foldamers combining features of peptides and triazolamers—repetitive peptidomimetic structures with triazoles replacing peptide bonds. We report on the synthesis of a new class of peptidomimetics, containing 1, 5‐disubstituted 1, 2, 3‐triazoles in an alternating fashion with amide bonds and the analysis of their conformation in solid state and solution. Homo‐ or heterochiral peptidotriazolamers were obtained from enantiomerically pure propargylamines with stereogenic centers in the propargylic position and α‐azido esters by ruthenium‐catalyzed azide–alkyne cycloaddition (RuAAC) under microwave conditions in high yields. With such building blocks the peptidotriazolamers are readily available by solution phase synthesis. While the conformation of the homochiral peptidotriazolamer Boc‐Ala [5Tz] Phe‐Val [5Tz] Ala‐Leu [5Tz] Val‐OBzl resembles that of a β VIa1 turn, the heterochiral peptidotriazolamer Boc‐d ‐Ala [5Tz] Phe‐d ‐Val [5Tz] Ala‐d ‐Leu [5Tz] Val‐OBzl adopts a polyproline‐like repetitive structure. Abstract : Stereochemistry matters : While the conformation of the homochiral peptidotriazolamer Boc‐Ala [5Tz] Phe‐Val [5Tz] Ala‐Leu [5Tz] Val‐OBzl resembles that of a βVIa1 turn, the heterochiral peptidotriazolamer Boc‐d ‐Ala [5Tz] Phe‐d ‐Val [5Tz] Ala‐d ‐Leu [5Tz] Val‐OBzl adopts a polyproline‐like repetitive structure.